2017
DOI: 10.1108/er-06-2016-0105
|View full text |Cite
|
Sign up to set email alerts
|

What are the consequences of a managerial approach to union renewal for union behaviour? A case study of USDAW

Abstract: Purpose -The purpose of this paper is to explore the consequences of a managerial approach to renewal for a union's behaviour by analysing the UK's fourth largest trade union -The Union of Shop, Distributive and Allied Workers (USDAW). Design/methodology/approach -The findings draw on in-depth semi-structured interviews with union officials. Findings -The research findings show the significance of a managerialist approach to UDSAW's renewal strategy and its correlation with existing renewal strategies of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…USDAW's renewal strategy combined organising (setting up its own organising academy in 2000) and a centralised, targeted approach to bargaining (Evans et al, 2017). The targeted approach focuses on the ‘big four’ supermarkets (Co-op, Morrisons, Sainsburys and Tesco).…”
Section: Sectoral Dynamics Of Collective Bargaining In Rail Transport and Food Retailmentioning
confidence: 99%
“…USDAW's renewal strategy combined organising (setting up its own organising academy in 2000) and a centralised, targeted approach to bargaining (Evans et al, 2017). The targeted approach focuses on the ‘big four’ supermarkets (Co-op, Morrisons, Sainsburys and Tesco).…”
Section: Sectoral Dynamics Of Collective Bargaining In Rail Transport and Food Retailmentioning
confidence: 99%
“…Its initial strategy was to train highly qualified and satisfied retail workers, leading to substantial gains in pay and job security for the union's membership (Kelly 2004). Yet even this partnership is under threat, as union members blame their leaders for pay and benefit concessions that were accepted to maintain the consultative tradition within the company (Evans et al 2017).…”
Section: Explaining Variation In Partnership Outcomesmentioning
confidence: 99%
“…Yet even this partnership is under threat, as union members blame their leaders for pay and benefit concessions that were accepted to maintain the consultative tradition within the company (Evans et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Most of the participants were not unionized and had tertiary qualifications (undergraduate and postgraduate). International scholars also found that educated employees are not unionized, and that management plays a role in discouraging the unionization of employees (Evans, Pyman & Byford, 2016). Prior to this study, there was no happiness index for HRM practitioners in South Africa, using the dimensions considered in this study.…”
Section: Discussionmentioning
confidence: 89%